PERAN LOGISTIK DAN RANTAI PASOK DALAM MENDUKUNG PENANGANAN DAN PENCEGAHAN STUNTING MENUJU INDONESIA EMAS 2045 - Zai, Yovita Yulia M. (JURNAL LENTERA BISNIS, 2025)
The purpose of this study was to determine the role of logistics and supply chains in supporting the handling and prevention of stunting towards Indonesia Emas 2045. This research approach collects data through literature studies, which involve reading literature from various sources including books, reports, articles, and journals using qualitative and deductive approaches. The findings in this study are that there are several roles of logistics and supply chains in supporting the handling and prevention of stunting towards Indonesia Emas 2045. The role of logistics in supporting the handling and prevention of stunting includes, distribution of nutritional and health products, storage and warehouse management, transportation management, and logistics monitoring and evaluation. Then the role of the supply chain in supporting the handling and prevention of stunting includes, national and local product availability, efficiency and sustainability, multi-sector partnerships and collaborations, and responsiveness to customer needs.